2012
DOI: 10.1002/pon.3082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a social cognitive theory‐based email intervention designed to influence the physical activity of survivors of breast cancer

Abstract: Email-based interventions based on SCT can significantly influence levels of self-reported physical activity of breast cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 31 publications
0
103
0
Order By: Relevance
“…Seven studies provided either a pedometer or accelerometer to participants. In seven cases, some form of behavior counseling was offered by phone [20, 27], by e-mail [30], in person [31, 32] or a combination of these [33-35]. Coaching strategies varied, but included activities such as in-person PA demonstrations [34, 35], counseling from a healthcare provider [35], supervised exercise sessions combined with cognitive-behavioral therapy [31], tailored counseling sessions [27] and group discussions about perceived barriers and goals related to PA [32, 36].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies provided either a pedometer or accelerometer to participants. In seven cases, some form of behavior counseling was offered by phone [20, 27], by e-mail [30], in person [31, 32] or a combination of these [33-35]. Coaching strategies varied, but included activities such as in-person PA demonstrations [34, 35], counseling from a healthcare provider [35], supervised exercise sessions combined with cognitive-behavioral therapy [31], tailored counseling sessions [27] and group discussions about perceived barriers and goals related to PA [32, 36].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the most effective technologies for changing PA behavior in cancer survivors are understudied and warrant further research. One pilot study using an email intervention demonstrated promising results for increasing PA behavior in breast cancer survivors (Hatchett, Hallam, & Ford, 2013). As research in this area grows, strategies for overcoming barriers related to suboptimal user engagement, privacy concerns, and limited Internet access PA AND CANCER SURVIVORSHIP RESEARCH for certain subgroups should be tested (Cavallo, Chou, McQueen, Ramirez, & Riley, 2014).…”
Section: What Are the Most Effective Pa Behavior Change Interventionsmentioning
confidence: 99%
“…In contrast to other studies, we had only one (2.3 %) dropout, showing good adherence and tolerance, whereas in a recent review the dropout rates ranged between 6 % and 45 % with similar intervention content [73]. home-based training settings [91,92]. To reduce such potential bias, we combined the subjective feedback (Borg rating for training sessions) with an objective measurement (average heart rate).…”
Section: Strengths and Limitationsmentioning
confidence: 99%